Successful treatment of recalcitrant juvenile pemphigus foliaceus with intravenous immunoglobulin and rituximab - Hock Gin Teo; Tzyy Huei Lim; Kin Fon Leong; Pubalan Muniandy (Wolters Kluwer Medknow Publications, 2022)
Pemphigus foliaceus (PF) is uncommon among children. The usage of rituximab in childhood PF is even less documented. We reported a case of a 16-year-old boy with juvenile PF who failed conventional treatments and was started on combination therapy of intravenous immunoglobulin (IVIG) and rituximab followed by six-monthly rituximab maintenance therapy. He achieved full remission and no adverse effects. Therefore, in cases of recalcitrant juvenile PF, combination therapy of IVIG and rituximab can be considered.